Trend analysis of software engineering scientific publications - Tengku Nadzirah, Tengku Majani (2019)
One of the most important problems for a researcher is how to identify the current trends and topics in the scientific publications. There is a diversity of specific keywords in the scientific journals and papers that had been published. The study aimed to analyse the existing methods and technique to predict trends of scientific publications. To get the suitable solution to the problem, this work proposes an implementation of the algorithm for trend analysis in Software Engineering scientific literature. The estimation of the future trend is done by development of the algorithm linear regression algorithm in Matlab. With data collected from the main Science Direct database with of Software Engineering keywords, validation of the proposed algorithms on the case study was done. The implementation of the algorithm will help the users to see the trends and recognize patterns in Software Engineering scientific publications in future. In Matlab, the study focused on linear regression Matlab code to achieve the desire results.